1998
DOI: 10.1159/000016499
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Erosion by Some Soft Drinks and Orange Juices Relative to Their pH, Buffering Effect and Contents of Calcium Phosphate

Abstract: The capability of a soft drink or a juice to erode dental enamel depends not only on the pH of the drink, but also on its buffering effect. As the latter is the ability of the drink to resist a change of pH it may add to the effects of the actual pH. The aim of the present study was to compare the pH and the buffering effect of various soft drinks with their erosive effects and the solubility of apatite. In 18 soft drinks, mineral waters and juices available on the Danish market, pH and the concentrations of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
262
4
71

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(355 citation statements)
references
References 21 publications
18
262
4
71
Order By: Relevance
“…Beverage compositions vary widely; the milieu of nutrients and nonnutrients likely influences the capacity for erosion [16,17]. Calcium and fluoride have been shown to limit the extent of erosion by saturating the solution and/or altering the solubility of enamel [1,9,12,14,18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Beverage compositions vary widely; the milieu of nutrients and nonnutrients likely influences the capacity for erosion [16,17]. Calcium and fluoride have been shown to limit the extent of erosion by saturating the solution and/or altering the solubility of enamel [1,9,12,14,18].…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro erosion potential of representative commercial beverages was evaluated using extracted human permanent teeth [9]. The in vitro model was selected because the intact enamel or dentin surface is exposed to the beverage and the model allows for observation of demineralization within a reasonable time period.…”
Section: Design and Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…a strong preventive effect upon dental erosion. 15 In addition, the naturally high levels of calcium in fi zzy mineral waters have been shown in the laboratory to inhibit hyroxyapatite dissolution. 16 Furthermore, an in vitro study has demonstrated that the addition of calcium to acidic candies results in a reduction of their capacity to bring about dental erosion.…”
Section: Introductionmentioning
confidence: 99%